Greenhouses and vermicomposting: a facilitator of the teaching and learning process - Vellani, Cassio Luiz; Presciliano, Vitor Matheus (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2025)
The integration between curricular components and an educational artifact—a vegetable greenhouse with vermicomposting—aims to enhance the teaching-learning process and foster interdisciplinarity in school education. Using the Design Science Research (DSR) method, routines were identified for various courses, such as Agronomy, Chemistry, and Tourism Management Technology, by linking the curriculum content to the elements of the greenhouse. The study was conducted at an educational institution, where the curricular components of multiple courses were mapped, and their potential connections with the proposed artifact were analyzed. As a result, 23 routines were identified for the Agronomy course, 2 for Systems Analysis and Development, 3 for Chemistry, 2 for Tourism Management Technology, 5 for Biological Sciences, 6 for the Integrated High School Agricultural Technician course, 1 for the Integrated High School Computer Technician course, and 5 for the Integrated High School Food Technician course. This approach proposes a practical teaching method, as it allows students to gain direct experience with the concepts learned in the classroom. This strategy not only promotes a deeper understanding of the content but also prepares students to tackle complex challenges in the labor market by encouraging a more holistic and interdisciplinary education. The study highlights the importance of seeking educational benefits through the integration of teaching, research, and outreach, enabling the advancement of practical knowledge in a specific field of study.